$\left| 2x-1 \right|=4x+5$ has how many numbers in its solution set?
Answer
Verified
442.2k+ views
Hint: Problems on solving equations of absolute values can be easily done by using the property of absolute values. We will take two cases into consideration for this problem. In the first case we consider a positive value of the term $2x-1$ and in the second case we consider the term $2x-1$ to be a negative one and solve both of the equations to get the solutions of the given equation.
Complete step by step solution:
The expression we have is
$\left| 2x-1 \right|=4x+5$
We apply the property of absolute value in the above equation to solve the equation.
First, we remove the absolute value term in the given equation. This creates two cases among which the first one is where we consider the positive value of the term $2x-1$ and in the second one is where we consider the term $2x-1$ to be negative one.
Therefore, the given equation becomes
$2x-1=4x+5......\left( \text{1} \right)$ , when $\left( 2x-1 \right)>0$
And $-\left( 2x-1 \right)=4x+5......\left( 2 \right)$ , when $\left( 2x-1 \right)<0$
Considering equation $\left( 1 \right)$ we get
$\Rightarrow 4x+5=2x-1$
Subtracting $2x$ from both the sides of the above equation we get
$\Rightarrow 4x+5-2x=2x-1-2x$
Further simplifying we get
$\Rightarrow 2x+5=-1$
Subtracting $5$ from both the sides of the above equation we get
$\Rightarrow 2x+5-5=-1-5$
Further simplifying we get
$\Rightarrow 2x=-6$
Dividing both sides of the above equation by $2$ we get
$\Rightarrow x=-\dfrac{6}{2}$
Further simplifying
$\Rightarrow x=-3$
Considering equation $\left( 2 \right)$ we get
$\Rightarrow 4x+5=-\left( 2x-1 \right)$
$\Rightarrow 4x+5=-2x+1$
Adding $2x$ to both the sides of the above equation we get
$\Rightarrow 4x+5+2x=-2x+1+2x$
Further simplifying we get
$\Rightarrow 6x+5=1$
Subtracting $5$ from both the sides of the above equation we get
$\Rightarrow 6x+5-5=1-5$
Further simplifying
$\Rightarrow 6x=-4$
Dividing both sides of the above equation by $6$ we get
$\Rightarrow x=\dfrac{-4}{6}$
$\Rightarrow x=-\dfrac{2}{3}$
Also, we put both the solutions in the given equation. The solution $x=-\dfrac{2}{3}$ satisfies the given equation but the solution $x=-3$ does not satisfy the given equation as the RHS becomes $-7$ , and any absolute value cannot be negative. Hence, the solution $x=-3$ is an extraneous one.
Therefore, the number of solutions in the equation’s solution set is one.
Note: We have to keep in mind that while removing the absolute term we have to take both the cases $\left( 2x-1 \right)>0$ and $\left( 2x-1 \right)<0$ into account so that we get all the solutions. Also, we must properly simplify the obtained equations so that mistakes are avoided.
Complete step by step solution:
The expression we have is
$\left| 2x-1 \right|=4x+5$
We apply the property of absolute value in the above equation to solve the equation.
First, we remove the absolute value term in the given equation. This creates two cases among which the first one is where we consider the positive value of the term $2x-1$ and in the second one is where we consider the term $2x-1$ to be negative one.
Therefore, the given equation becomes
$2x-1=4x+5......\left( \text{1} \right)$ , when $\left( 2x-1 \right)>0$
And $-\left( 2x-1 \right)=4x+5......\left( 2 \right)$ , when $\left( 2x-1 \right)<0$
Considering equation $\left( 1 \right)$ we get
$\Rightarrow 4x+5=2x-1$
Subtracting $2x$ from both the sides of the above equation we get
$\Rightarrow 4x+5-2x=2x-1-2x$
Further simplifying we get
$\Rightarrow 2x+5=-1$
Subtracting $5$ from both the sides of the above equation we get
$\Rightarrow 2x+5-5=-1-5$
Further simplifying we get
$\Rightarrow 2x=-6$
Dividing both sides of the above equation by $2$ we get
$\Rightarrow x=-\dfrac{6}{2}$
Further simplifying
$\Rightarrow x=-3$
Considering equation $\left( 2 \right)$ we get
$\Rightarrow 4x+5=-\left( 2x-1 \right)$
$\Rightarrow 4x+5=-2x+1$
Adding $2x$ to both the sides of the above equation we get
$\Rightarrow 4x+5+2x=-2x+1+2x$
Further simplifying we get
$\Rightarrow 6x+5=1$
Subtracting $5$ from both the sides of the above equation we get
$\Rightarrow 6x+5-5=1-5$
Further simplifying
$\Rightarrow 6x=-4$
Dividing both sides of the above equation by $6$ we get
$\Rightarrow x=\dfrac{-4}{6}$
$\Rightarrow x=-\dfrac{2}{3}$
Also, we put both the solutions in the given equation. The solution $x=-\dfrac{2}{3}$ satisfies the given equation but the solution $x=-3$ does not satisfy the given equation as the RHS becomes $-7$ , and any absolute value cannot be negative. Hence, the solution $x=-3$ is an extraneous one.
Therefore, the number of solutions in the equation’s solution set is one.
Note: We have to keep in mind that while removing the absolute term we have to take both the cases $\left( 2x-1 \right)>0$ and $\left( 2x-1 \right)<0$ into account so that we get all the solutions. Also, we must properly simplify the obtained equations so that mistakes are avoided.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
Fill the blanks with the suitable prepositions 1 The class 9 english CBSE
How do you graph the function fx 4x class 9 maths CBSE
Name the states which share their boundary with Indias class 9 social science CBSE
Difference Between Plant Cell and Animal Cell
What is pollution? How many types of pollution? Define it
What is the color of ferrous sulphate crystals? How does this color change after heating? Name the products formed on strongly heating ferrous sulphate crystals. What type of chemical reaction occurs in this type of change.